Nurturing Grandchildren With Down Syndrome: A Qualitative Study on Grandparents’ Needs Using Digital Tools† - Sánchez Gómez, María C.; Martín-Sevillano, Rocío; Martín-Cilleros, María V.; Marcos, J. J. Mena; García-Peñalvo, Francisco J. (Frontiers in Psychology, 2021)
Grandparents who have grandchildren with disabilities are an underrepresented group in existing research related to the field. This qualitative phenomenological study’s general purpose is to analyze, from a personal perspective, the situations and needs of grandparents who have grandchildren with Down syndrome. The participants’ ages range from 65 to 85, and the ages of their grandchildren with Down syndrome range from 3 to 21 years. All participants had one grandchild with a disability, except for two, who each had two. A sociodemographic questionnaire was administered, and individual interviews were conducted, using open questions, through phone and/or video calls. An analysis of the participants’ speech was carried out, which implied the development of a system of meta-categories and categories. This analysis was developed manually, given the COVID-19 environment. The results indicate a substantial change from negative feelings caused by the knowledge of the diagnosis to feelings related to positive experiences expressed currently. The participants themselves as a fundamental source of support (informal, instrumental, practical, social, emotional, and economic) for their families and, mainly, for their grandchildren with Down syndrome. A need for information and training was observed when the grandparents talked about first being informed of the diagnosis and their concerns about the future of these grandchildren and their siblings. They made social demands, such as greater government involvement or more significant opportunities to access resources and rights for their grandchildren. The results are discussed, as are possible future research directions.